Impact of Online Recruitment on Organizational Attractiveness: An Experimental Study in the Context of Pakistan - Qamar Ali; Muhammad Naveed Aslam; Sahar Hafeez (iRASD Journal of Management)
The purpose of this study is to explore the aesthetical features of corporate recruitment websites, including the website design, style, and color, and to investigate their impact on organizational attractiveness and applicants' intention to apply. By doing so, the study also examines the effects of corporate websites on applicants' perception of the corporate culture and measures the mediating impact of perceptions of organizational culture on organizational attractiveness and applicants' intention to apply for the jobs in the context of Pakistan. The study is based on a laboratory experiment with three hundred undergraduate business students conducted at a university computer lab. Correlation, Independent T-test, One-way ANOVA, and Simple Linear Regression were applied to analyze variables using SPSS. The findings of this study support the hypothesis that website features have a significant positive impact on applicants' perceived organizational attractiveness. However, the website's design does not seem to impact applicants' intentions to apply for the job substantially. The regression analysis results also revealed that the perceived organizational culture partially mediates the relationship between website features and organizational attractiveness and fully mediates the relationship between website features and intentions to Apply.